A day at the police station. - Scarry, Richard (New York : Golden Books, 2004)
Bridget spends a day at work with her father, Sergeant Murphy, and learns what an important job being a police officer is.
Keywords: Police -- Fiction; Police stations -- Fiction; Fathers and daughters -- Fiction; Dogs -- Fiction; Animals -- Fiction